Padrões discursivos nas rodas de conversa : avaliação de movimentos e práticas epistêmicas - Silva, Rosianne Pereira (2021)
This research sought to verify the existence of movements and epistemic practices in Chatting Circles and what are the relationships between these epistemic operations in the teaching and learning processes. To achieve this objective, we sought to characterize and observe patterns about possible relationships between the actions of a teacher and students from two classes of the 7th year of Elementary Education in Chatting Circles (RC). The teacher's actions were characterized by the epistemic movements carried out during the teaching process and the students' actions were characterized by the epistemic practices. To characterize epistemic movements and practices, specific analytical tools for discursive interactions were used. As a result, there is evidence that the teacher's actions using the Chatting Circles proved to be effective in performing epistemic movements, since seven categories were identified among those contemplated by the analytical tool in one of the RC episodes and at least five in the other episodes. analyzed for both classes Regarding the epistemic practices, it was found that the Chatting Circles proved to be conducive to their occurrences, given that in view of the actions developed by the teacher, it was observed the students' engagement in the proposed activity in a kind of chain of actions. This engagement is related to the teacher's epistemic movements and to the epistemic practices developed by the students themselves. We recorded in the Round of Conversation episodes; practices contemplated by the 3 social instances provided for in Jimenez Aleixandre's tool. Finally, the relationships identified between movements and epistemic practices were verified, which allowed us to conclude that the teacher's actions generate epistemic practices in students and that, also, these operations are also generated by the actions of students themselves inserted in the Chatting Circles, being the occurrence of movements and epistemic practices an instrument that allows the sharing of experiences and the development of reflections on the subjects' educational practices. The teaching and learning processes are based on interactions between peers, through internal dialogues and observation and reflection possible for both parties (teacher and students).